Analisis Konflik Pemerintah Daerah Dengan Masyarakat Dalam Aktivitas Pertambangan Emas Ilegal Di Desa Hutabargot Nauli Kabupaten Mandailing Natal - Mora, Linda; Arifin, Zainal; Valentina, Tengku RIka (Indonesian Democracy Research Center, 2023)
This article aims to analyze how the conflict between the local government and the community in illegal gold mining activities in Hutabargot Nauli village, Hutabargot district, Mandailing Natal district, namely what caused the conflict, what caused the conflict to persist, and why until now the local government has not been able to close it. This research is a research using literature study method or literature review. The results of this paper indicate that the closure of illegal gold mining activities in the village of Hutabarkot Nauli cannot be carried out by the local government because the community will continue to reject the appeal from the local government and conflicts that occur between the local government and the community will not have a solution to resolve it.